PENGARUH TEKA-TEKI SILANG BERGAMBAR TERHADAP KEMAMPUAN BAHASA ANAK KELOMPOK B DI TK AMARTA TANI BANDAR LAMPUNG - Nabila Agelia Putri; Hetty Anggraini; Tri Dewantari; Sulistianah (Renjana Pendidikan Dasar, 2023)
This research is motivated by children's language skills that have not developed as expected. Children's language skills include mastery of children's vocabulary which is still lacking, lack of interest in reading, and children's writing abilities that have not yet developed. The formulation of the problem in this research is Is there an effect of pictorial crossword puzzles on the language skills of group B children at Kindergarten Amarta Tani Bandar Lampung. The aim of this study was to explain the effect of crossword puzzles on speaking, reading, and writing skills of group B children at Kindergarten Amarta Tani Bandar Lampung. This study was a pre-experimental design. The sample in this study consisted of 10 children in the experimental class. Data collection was obtained by means of observation and documentation. Data analysis and hypothesis testing in this study used the Mann Wilcoxon test because the research data is ordinal data. From the results of the analysis of the Mann Wilcoxon test, it was obtained from the post-test results of the experimental class. For the ability to speak the value of Sig. (0.00 <0.05) and supported by the average of (experimental class = 4.18), for reading ability the value of Sig was obtained. (0.00 < 0.05) and supported by the average of (experimental class = 4.18), for writing ability the value of Sig was obtained. (0.00 <0.05) and supported by the average of (experimental class = 4.18). So from the three results of the problem formulation above it can be concluded that Ha is accepted, so there is an influence of pictorial crossword puzzles on the language skills of group B children in Kindergarten Amarta Tani Bandar Lampung.